Students' Attitudes Towards Hate Speech in the Use of Social Media - Utami, Ichwani Siti; Kurnia, Heri; Hendri, Hendri (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study aims to analyze the level of students' attitudes toward hate speech on social media and the factors that influence students' attitudes toward hate speech. This study used a quantitative descriptive approach with a survey method. The study population was all tenth-grade students of Nusantara Plus Senior High School, Ciputat, South Tangerang, with a sample of 70 students. The research instrument in this study was a questionnaire whose validity and reliability were tested. Data were analyzed using normality tests and one-tailed t-tests with the help of the Statistical Package for the Social Sciences version 2.0. The results of the study indicate that the level of students' attitudes toward hate speech is in the very low category, with an average score of 143.21, lower than the limit value of 294. Students' attitudes toward hate speech are influenced by a conducive school environment, parental supervision, and sufficient understanding of digital communication ethics. The results of this study emphasize the important role of schools and families in preventing negative behavior on social media through digital literacy development and strengthening tolerance values.